2014
DOI: 10.2133/dmpk.dmpk-13-rg-102
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Glucuronidation of Oxyresveratrol, a Natural Hydroxystilbene, by Human Liver and Intestinal Microsomes and Recombinant UGTs

Abstract: Oxyresveratrol (OXY) is a natural hydroxystilbene that shows similar bioactivity but better water solubility than resveratrol. This study aims to characterize its glucuronidation kinetics in human liver (HLMs) and intestinal (HIMs) microsomes and identify the main UDP-glucuronosyltransferase (UGT) isoforms involved. Three and four mono-glucuronides of OXY were generated in HIMs and HLMs, respectively, with oxyresveratrol-2-O-β-D-glucuronosyl (G4) as the major metabolite in both organs. The kinetics of G4 forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…However, this compound poses a challenge for development into a phytopharmaceutical product due to its poor pharmacokinetic profile. This problem is a common phenomenon of lead compounds from natural resources, especially low oral bioavailability due to extensive metabolism in the gastrointestinal tract [11, 14, 24]. The goal of this study was to determine whether the pharmacokinetic profile of oxyresveratrol could be improved by combination with piperine, which acts as a bioenhancer in rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, this compound poses a challenge for development into a phytopharmaceutical product due to its poor pharmacokinetic profile. This problem is a common phenomenon of lead compounds from natural resources, especially low oral bioavailability due to extensive metabolism in the gastrointestinal tract [11, 14, 24]. The goal of this study was to determine whether the pharmacokinetic profile of oxyresveratrol could be improved by combination with piperine, which acts as a bioenhancer in rats.…”
Section: Discussionmentioning
confidence: 99%
“…ORV is then quickly absorbed and undergoes hepatic conjugation to provide ORV 2- O -β-D-glucuronide and ORV sulfate. A further study using human liver and intestinal microsomes revealed that 2- O -β-D-glucuronide is the major metabolite, and UDP-glucuronosyltransferases (UGTs) are the enzymes involved in the transformation [ 282 ].…”
Section: Pharmacokinetic Profilementioning
confidence: 99%
“…However, the therapeutic effect of OXY administered via the oral route is limited due to its poor intestinal permeability and efflux pump transport involving P-glycoprotein and multidrug resistance proteins [14]. In addition, OXY undergoes first-pass metabolism and rapid elimination in both intestine and liver resulting in very low oral bioavailability [15][16]. The extensive metabolism of OXY leads to the formation of glucuronide and sulfate conjugates and subsequent loss of biological activity [17].…”
Section: A Self-microemulsifying Formulation Of Oxyresveratrol Prevenmentioning
confidence: 99%